BIOCHEMICAL INDICES OF INFLAMMATION, ENDOGENOUS INTOXICATION, FIBRO-SIS, CHOLESTASIS AT PATIENTS WITH DIF-FERENT FORMS OF CHRONIC PANCREATITIS - Krylova, O.; Sogina, T.; Shevchenko, B.; Ratchik, V. (World of Medicine and Biology, 2010)
The study included 71 patients with chronic pancreatitis (41 of them – with cyst of the pancreas). It was found that patients with chronic pancreatitis characterized by endogenous intoxication, fibrosis, cholestasis, breach of the lipid metabolism, increasing the number of copper and reduction of calcium in the blood serum. All patients with chronic pancreatitis with cyst had significantly higher levels of endogenous intoxication and more severe inflammatory and destructive processes in the body.
Keywords: chronic pancreatitis; endogenous intoxication; cholestasis; fibrosis